2001
DOI: 10.1300/j229v01n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Seizure Variables, But Not Hypnotizability or Dissociation, Differentiated Psychogenic from Organic Seizures

Abstract: ABSTRACT. Early detection and differential diagnosis of psychogenic non-epileptic seizures (PNES) and epileptic seizures (ES) is a major clinical issue in comprehensive epilepsy centers. Using blind conditions with patients with PNES (N = 10) and ES (N = 31) before diagnosis, we tested the hypotheses that individuals with PNES would exhibit significantly greater dissociativity, hypnotizability, absorption, and history of early abuse than ES patients. Although PNES patients tended to show greater dissociative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Only a few scientific papers have been published on the association of hypnotizability and somatoform disorders (Kuyk, Spinhoven, & van Dyck, 1999;Roelofs et al, 2002). These studies are congruent with earlier clinical observations in that somatoform disorder patients are more hypnotizable than matched patient controls, although this relation is equivocal (Litwin & Cardeña, 2000;Moene, Spinhoven, Hoogduin, Sandyck, & Roelofs, 2001). These studies further show a positive correlation between hypnotizability and the number of conversion complaints in a patient sample.…”
Section: Jarred W Younger Et Alsupporting
confidence: 74%
“…Only a few scientific papers have been published on the association of hypnotizability and somatoform disorders (Kuyk, Spinhoven, & van Dyck, 1999;Roelofs et al, 2002). These studies are congruent with earlier clinical observations in that somatoform disorder patients are more hypnotizable than matched patient controls, although this relation is equivocal (Litwin & Cardeña, 2000;Moene, Spinhoven, Hoogduin, Sandyck, & Roelofs, 2001). These studies further show a positive correlation between hypnotizability and the number of conversion complaints in a patient sample.…”
Section: Jarred W Younger Et Alsupporting
confidence: 74%
“…Some studies have reported higher rates of hypnotizability in patients with conversion disorders as compared to controls or patients with other pathological states (e.g. affective disorders) [6,35,53], while others have shown no difference in both hypnotizability and absorption (defined as the tendency to become fully involved in a perceptual, imaginative, or ideational experience) between patients with conversion disorders and controls [37]. A last study showed higher level of absorption in control subjects as compared to patients [23].…”
Section: Hypnosis As a Substitute For Hysteria?mentioning
confidence: 97%
“…The level of hypnotizability was shown to correlate with the number of conversion symptoms presented by patients [53]. For example, pseudo-epileptic patients (defined by the demonstration of paroxysmal involuntary behavior patterns mimicking epileptic events) were shown to present more dissociative symptoms as compared to epileptic patients [23,37]. Some studies have reported higher rates of hypnotizability in patients with conversion disorders as compared to controls or patients with other pathological states (e.g.…”
Section: Hypnosis As a Substitute For Hysteria?mentioning
confidence: 99%
“…This and related work on acute stress and post-traumatic stress disorders led to the refined hypothesis that high hypnotic suggestibility is a predisposing factor for dissociative psychopathology (Butler, Duran, Jasiukaitis, Koopman, & Spiegel, 1996). Attempts to test the hypothesized relationship between dissociative tendencies and hypnotic suggestibility in non-clinical samples have been mixed (e.g., Butler & Bryant, 1997;Dienes, Brown, Hutton, Kirsch, Mazzoni, & Wright, 2009), whereas patients reporting dissociative symptomatology have consistently displayed higher hypnotic suggestibility than control samples (Bryant, Guthrie, & Moulds, 2001;Roelofs, Hoogduin, Keijsers, Naring, Moene, & Sandijck, 2002;Spiegel, Hunt, & Dondershine, 1988; but see Litwin & Cardeña, 2000). These disparities may reflect the circuitous route by which dissociative tendencies influence hypnotic responding.…”
Section: Introductionmentioning
confidence: 99%